Impacto del turismo en el crecimiento económico de las regiones del Perú, durante el periodo 2017 – 2019 - Flores Metzger, Gianella Noruska (2022)
Tourism is one of the most important economic sectors of a country because it is an activity that promotes development and this development is derived from the correct use of the different tourist routes that a country has, and from the various benefits that it offers, which make it possible the economic development of various regions of a country. On the other hand, the contribution of tourism is good for any economy of a country because it has an impact on certain sectors such as employment, trade, income, culture and taxes. The main motivation of this research is to try to find the correlation and possible effect of tourism on the economic growth of the various departments of Peru, and in this way to try to understand the importance of tourism for the regional economies of the country. In our results we find that there is a positive effect of tourism on the economic growth of the various departments of Peru, specifically an increase of one million tourists increases the economic growth of the departments of Peru by approximately 0.4%, on the other hand also we found a negative correlation between tourism and the level of poverty in the departments of Peru, and a positive and high correlation between tourism and commerce (99%).